2021
DOI: 10.1021/acs.jpcc.1c06887
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol on Graphite: Ordered Structures and Delicate Balance of Interfacial and Intermolecular Forces

Abstract: Clear knowledge of solid–molecule interfacial structures is essential to the understanding of interfacial phenomena and the interplay of surface effects and intermolecular forces. Molecules that can form hydrogen bonds are of particular interest. Here, we report the structures and phase-transition behavior of (sub)­nanometer thick ethanol assemblies deposited on highly orientated pyrolytic graphite. Depending on the film thickness and temperature, three ordered structures of ethanol are observed: first, an int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 57 publications
2
5
0
Order By: Relevance
“…The results shown in Figure show that the suction/pulling force acting on the ethanol presents a molecular orientation dependence, findings which correspond to those found in the literature. The ethanol adhesion on graphitic samples observed here has also been confirmed by experiments and molecular synamics simulations. ,, Shin et al reported that ethanol molecules concentrate within a 10 Å open-edge GC, where a slightly higher ethanol density close to the GC center and edges is noted in their results. Even when ambient temperature was used with the simulations, the higher ethanol density at the GC edges and center is in qualitative agreement with the findings in this study.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The results shown in Figure show that the suction/pulling force acting on the ethanol presents a molecular orientation dependence, findings which correspond to those found in the literature. The ethanol adhesion on graphitic samples observed here has also been confirmed by experiments and molecular synamics simulations. ,, Shin et al reported that ethanol molecules concentrate within a 10 Å open-edge GC, where a slightly higher ethanol density close to the GC center and edges is noted in their results. Even when ambient temperature was used with the simulations, the higher ethanol density at the GC edges and center is in qualitative agreement with the findings in this study.…”
Section: Resultssupporting
confidence: 82%
“…In another molecular dynamics contribution by Zhao and Yang, the authors studied confined liquid ethanol within graphene layers and found that ethanol molecules change their orientation within the GC from laying to standing on the surface as the interlayer distance increases from 7 to 15 Å. He and Yang used reflection high-energy electron diffraction experiments to study a molecular thin film of ethanol on graphene. They showed that ethanol molecules lay on the surface in an ordered structure for a thin ethanol layer.…”
Section: Resultsmentioning
confidence: 99%
“…Shown in panels a–d of Figure are the reflection high-energy electron diffraction (RHEED) images of annealed 3 nm thick vapor-deposited ethanol [on highly oriented pyrolytic graphite (HOPG)] and methanol [on smooth InAs(111)] as well as their respective crystal structures. The temperature- and thickness-dependent structural evolutions of ethanol and methanol thin films have been reported previously. , Here, the attention is focused on the structural differences and crystallinity of the films. The two molecular solids share many similarities, including mass density, hydrogen-bonded (HB) chains that are infinitely extended along only one crystal axis, aliphatic vdW forces between adjacent chains to form a 2D molecular sheet, and vdW interactions between stacked layers along the out-of-plane direction.…”
mentioning
confidence: 85%
“…Shown in Figure are the RHEED and UED images of a 25 nm ethanol thin film, annealed up to 120 K and then maintained at 100 K. The increase in the horizontal diffraction width in panels b and c results from the use of a moderately converging beam (to minimize the electron footprint on the sample), which leads to its diverging downstream on the imaging device. The clear center diffraction streak without a narrow vertical width signifies the 2D-layered nature of the ethanol assembly lacking a well-defined stacking order between layers . Following the heating impulse of the supporting HOPG, a decrease in the intensity is observed along the streak, which signifies an increase in out-of-plane molecular motions that perturb the equilibrium lattice order observed in the top nanometers of the thin film.…”
mentioning
confidence: 98%
See 1 more Smart Citation